Peer2ref: a peer-reviewer finding web tool that uses author disambiguation - Andrade-Navarro, Miguel A; Palidwor, Gareth A; Perez-Iratxeta, Carol (Université d'Ottawa | University of Ottawa, 2012)
Abstract Background Reviewer and editor selection for peer review is getting harder for authors and publishers due to the specialization onto narrower areas of research carried by the progressive growth of the body of knowledge. Examination of the literature facilitates finding appropriate reviewers but is time consuming and complicated by author name ambiguities. Results We have developed a method called peer2ref to support authors and editors in selecting suitable reviewers for scientific manuscripts. Peer2ref works from a text input, usually the abstract of the manuscript, from which important concepts are extracted as keywords using a fuzzy binary relations approach. The keywords are searched on indexed profiles of words constructed from the bibliography attributed to authors in MEDLINE. The names of these scientists have been previously disambiguated by coauthors identified across the whole MEDLINE. The methods have been implemented in a web server that automatically suggests experts for peer-review among scientists that have authored manuscripts published during the last decade in more than 3,800 journals indexed in MEDLINE. Conclusion peer2ref web server is publicly available at http://www.ogic.ca/projects/peer2ref/ .